Siccibacter colletis as a member of the plant growth-promoting rhizobacteria consortium to improve faba-bean growth and alleviate phosphorus deficiency stress - Chamkhi, Imane; Zwanzig, Jessica; Ibnyasser, Ammar; Cheto, Said; Geistlinger, Joerg; Saidi, Rym; Zeroual, Youssef; Kouisni, Lamfeddal; Bargaz, Adnane; Ghoulam, Cherki (Frontiers in Sustainable Food Systems, 2023)
The rhizosphere is a hot spot and a source of beneficial microorganisms known as plant growth-promoting rhizobacteria (PGPR). From the alfalfa (Medicago sativa) rhizosphere, 115 bacteria were isolated, and from the screening for PGP traits, 26 interesting isolates were selected as PGP rhizobacteria for the next tests. The objective of this study was to use a consortium of PGPR to enhance the growth of faba-bean under phosphate (P) deficiency by taking advantage of their ability to release phosphorus from rock phosphate (RP). Several examined strains were found to have a relatively high activity on P solubilization, auxin, siderophore, ammoniac production, antifungal activity, and the ability to tolerate hypersalinity and water stress. 16S rRNA gene sequencing of the collection revealed six different genera, including Bacillus (46.15%), Siccibacter (23.07%), and Acinetobacter (15.38%) which were identified as the most abundant. Three of the interesting strains (Siccibacter colletis, Enterobacter huaxiensis, and Pantoea sp.) showed high plant growth promotion traits and no antagonism with Rhizobium laguerreae. These three bacteria were retained to establish a rhizobia-including consortium. The inoculation of faba-bean plants with the consortium improved growth parameters as root and shoot dried biomasses and some physiological criteria (chlorophyll content and P uptake under low P availability conditions), and the increase reached 40%. Our study could be the first report of faba-bean growth promotion by a multi-strain PGPR-rhizobia consortium involving S. colletis, E. huaxiensis, and Pantoea sp. Thus, this consortium could be recommended for faba-bean inoculation, particularly under P-limiting conditions.